Housing market risk in the European Union - Stepanyan, Rudolf (2020)
This bachelor thesis focuses on the current state of the housing market in the European Union. The main aim of this thesis is to find out if countries with lowest housing market corrections during the Great Recession pose the highest risk at the moment. In the first chapter the theory of the real estate cycles and corrections in the housing market during the Great Recession is described. The second chapter deals with the current housing market risk in the EU (Austria, Belgium, Finland, Germany, Sweden) and its potential driver.